Tuberculosis among Aboriginal and Nonaboriginal Persons in British Columbia - L Wang; K Noertjojo; RK Elwood; J Mark FitzGerald (Canadian Respiratory Journal)
OBJECTIVE: To compare cases of tuberculosis (TB) diagnosed among aboriginal persons with a random sample of nonaboriginal persons diagnosed with TB, and evaluate the trends in rates of disease between both groups during the same period.